Między oryginalnością a konwencją - Żuraszek-Ryś, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This present paper is the result of reflection on the lexical layer of the Balkan novels by Teodor Tomasz Jeż, separated from a group of twelve works consisting of artistic texts with similar themes and belonging to the same genre, thus representing similar linguistic-stylistic patterns: "Szandor Kowacz", "Asan", "Uskoki", "Narzeczona harambaszy", "Dachijszczyzna", "Zarnica", "Słowiański hercog", "Rotułowicze", "Lat temu dwieście", "W zaraniu", "Miłość w opałach" and "Rycerz chrześcijański".
Keywords: Jeż, Teodor Tomasz (1824-1915); idiolekt; literatura polska; powieść; słownictwo; tematy i motywy; kraje bałkańskie; Polish literature; novel; vocabulary; themes and motifs